Listening and Voice: Phenomenologies of Sound - Ihde, Don 1934- (New York State University of New York Press, 2007)
Listening and Voice is an updated and expanded edition of Don Ihde's groundbreaking 1976 classic in the study of sound. Ranging from the experience of sound through language, music, religion, and silence, clear examples and illustrations take the reader into the important and often overlooked role of the auditory in human life. Ihde's newly added preface, introduction, and chapters extend these sound studies to the technologies of sound, including musical instrumentation, hearing aids, and the new group of scientific technologies which make infra- and ultra-sound available to human experience.
Keywords: Music philosophy and esthetics; Phenomenology